A new straightforward method for measuring xylene soluble for high impact polypropylene. (12th December 2016) - Boyron, Olivier; Cancelas, Aarón J.; Taam, Manel; Boisson, Christophe; McKenna, Timothy
Abstract: The determination of the xylene soluble fraction in high impact polypropylene is used to estimate the rubber content in the polymer material. In analytical laboratories, the soluble fraction is measured by solvent extraction using gravimetric methods according to ASTM5492 or ISO6427. These methods require a large quantity of polymers, large volume of solvent, and long extraction times. It is therefore highly desirable to develop other laboratory methodologies for this task; preferably methodologies that employ existing laboratory equipment. It is found that the SEC method proposed here yields estimates of rubber contents very close to those found using standardized technics but in much shorter times. Abstract : In analytical laboratory, rubber content in a high impact polypropylene is determined by xylene soluble fraction using the gravimetric method. This value is proportional to the amorphous content of the materials. It is widely used for product quality control or monitoring properties of the polymer. In this paper, we describe a new method based on the use of size exclusion chromatography for measuring the amount of rubber present in copolymer. The obtained data are compared to the conventional ASTM testing method.